2008
DOI: 10.1007/s12230-008-9045-z
|View full text |Cite
|
Sign up to set email alerts
|

Interval Mapping of Quantitative Trait Loci for Corky Ringspot Disease Resistance in a Tetraploid Population of Potato (Solanum tuberosum subsp. tuberosum)

Abstract: Corky ringspot disease (CRS) resistance is an ideal target trait for breeding using marker-assisted selection (MAS) due to the high variability in field disease incidence that complicates screening for resistance. To develop molecular marker(s) associated with CRS resistance, a linkage map was constructed for a tetraploid population of 92 genotypes in order to conduct quantitative trait locus (QTL) analysis. The population was tested for CRS resistance in an infested screening field for four years. Broad sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The findings we have presented, along with the recent work of Bradshaw et al (2008), Khu et al (2008), and Sagredo et al (2006) have demonstrated both the challenges and the feasibility of studying potato genetics using tetraploid potatoes.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The findings we have presented, along with the recent work of Bradshaw et al (2008), Khu et al (2008), and Sagredo et al (2006) have demonstrated both the challenges and the feasibility of studying potato genetics using tetraploid potatoes.…”
Section: Discussionmentioning
confidence: 76%
“…The fi ndings we have presented, along with the recent work of Bradshaw et al (2008), Khu et al (2008), and Sagredo et al (2006) have demonstrated both the challenges and the feasibility of studying potato genetics using tetraploid potatoes. We have provided corroborating evidence for the presence of foliage maturity QTL on chromosomes III and V; QTL for specifi c gravity and/or dry matter on chromosomes II, V, VIII, IX, and XI; and QTL for yield on chromosomes II, V, VI, and VIII.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The genotype 95‐608 is a genotype derived from the synthetic cultivar CUF 101 (Lehman et al, 1983). Several genetic linkage maps of tetraploid alfalfa (Julier et al, 2003; Robins et al, 2007; Sledge et al, 2005) and potato ( Solanum tuberosum L.) (Bradshaw et al, 2008; Khu et al, 2008; McCord et al, 2011) were generated using F 1 populations given the outcrossing and autotetraploid nature of these species. Theoretical models for gene segregation in F 1 populations of autotetraploid species were developed by Wu et al (2001) and Luo et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…Linkage and QTL analysis were performed using the TetraploidMap software (Hackett et al, 2007) previously used for mapping in tetraploid alfalfa (Julier et al, 2003; Robins et al, 2007, 2008) and tetraploid potato (Bradshaw et al, 2008; Khu et al, 2008). The parental genotypes were determined based on the observed parent and offspring marker score (Luo et al, 2000).…”
Section: Methodsmentioning
confidence: 99%